2009
DOI: 10.3109/03630260903217141
|View full text |Cite
|
Sign up to set email alerts
|

Risk/Benefit Assessment, Advantages Over Other Drugs and Targeting Methods in the Use of Deferiprone as a Pharmaceutical Antioxidant in Iron Loading and Non Iron Loading Conditions

Abstract: Tissue damage caused by oxidative stress is a common characteristic of many conditions involving different major organs such as the brain, heart, liver and kidneys. The treatment of such conditions using classical antioxidants is not in most cases sufficient or effective because it lacks specificity and has a low therapeutic index. Increased evidence from in vitro, in vivo and clinical studies suggest that deferiprone (L1) can be used as a potent pharmaceutical antioxidant by mobilizing labile iron and copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 15 publications
3
31
0
1
Order By: Relevance
“…The proposed mechanism for the mode of action of L1 was removal of localised excess deposited iron and inhibition of the iron induced catalytic activity and free radical cascades which caused increase in oxidative stress and cellular damage. This proposal was based on in vitro findings, animal studies and clinical results suggesting that L1 had access to all major organs and tissues including the heart and the brain [5,69,70] . The ability of L1 to remove excess deposited iron from the hearts of FA patients similar to TM patients, was also suggested since focal or gross iron overload appears to be the main cause of mortality in both diseases [5,69,70] .…”
Section: The Role Of Deferiprone In the Treatment Of Friedreich Ataxiamentioning
confidence: 99%
See 4 more Smart Citations
“…The proposed mechanism for the mode of action of L1 was removal of localised excess deposited iron and inhibition of the iron induced catalytic activity and free radical cascades which caused increase in oxidative stress and cellular damage. This proposal was based on in vitro findings, animal studies and clinical results suggesting that L1 had access to all major organs and tissues including the heart and the brain [5,69,70] . The ability of L1 to remove excess deposited iron from the hearts of FA patients similar to TM patients, was also suggested since focal or gross iron overload appears to be the main cause of mortality in both diseases [5,69,70] .…”
Section: The Role Of Deferiprone In the Treatment Of Friedreich Ataxiamentioning
confidence: 99%
“…This proposal was based on in vitro findings, animal studies and clinical results suggesting that L1 had access to all major organs and tissues including the heart and the brain [5,69,70] . The ability of L1 to remove excess deposited iron from the hearts of FA patients similar to TM patients, was also suggested since focal or gross iron overload appears to be the main cause of mortality in both diseases [5,69,70] . Similarly, it was also suggested that the application of L1 was a more appropriate therapy than the use of antioxidants for the toxicity arising from focal or localised excess deposited iron and also that the therapeutic options included drug combinations [5,69,70] .…”
Section: The Role Of Deferiprone In the Treatment Of Friedreich Ataxiamentioning
confidence: 99%
See 3 more Smart Citations